Social learning for climate resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
With collaborative, adaptive learning approaches, researchers and stakeholders can tackle complexity and uncertainty together.